1993
DOI: 10.1056/nejm199305063281804
|View full text |Cite
|
Sign up to set email alerts
|

Cyclospora Species -- A New Protozoan Pathogen of Humans

Abstract: We have identified organisms of the genus cyclospora that are remarkably similar to cryptosporidia in their morphologic features and the diarrheal disease that they produce in humans. The complete life cycle and epidemiology of this new protozoan parasite remain to be described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
217
1
35

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 396 publications
(257 citation statements)
references
References 15 publications
4
217
1
35
Order By: Relevance
“…Cyclospora cayetanensis is more closely related genetically to Eimeria species than to Cryptosporidium species (5), and the two organisms have biological differences. For example, C. parvum is infectious when excreted and can be transmitted directly from person to person; Cyclospora cayetanensis requires a period of time in the environment to sporulate into the infectious form (3), decreasing the likelihood of direct person-to-person spread. Cryptosporidium parvum infects both humans and a variety of mammals (6), and evidence is mounting that non- parvum zoonotic Cryptosporidium species can also infect immunocompetent humans (7,8).…”
mentioning
confidence: 99%
“…Cyclospora cayetanensis is more closely related genetically to Eimeria species than to Cryptosporidium species (5), and the two organisms have biological differences. For example, C. parvum is infectious when excreted and can be transmitted directly from person to person; Cyclospora cayetanensis requires a period of time in the environment to sporulate into the infectious form (3), decreasing the likelihood of direct person-to-person spread. Cryptosporidium parvum infects both humans and a variety of mammals (6), and evidence is mounting that non- parvum zoonotic Cryptosporidium species can also infect immunocompetent humans (7,8).…”
mentioning
confidence: 99%
“…En 1994, cuando Ortega y Cryptosporidium, Isospora, Cyclospo'ra y colaboradores describieron el parásito como Microspora, se han descrito como causa de Cyclospora cayetanensis (1 O), se confirmó que en patología intestinal tanto en los pacientes con el intestino existían formas intraepiteliales del alteraciones de la inmunidad como en personas parásito en su estado asexual en las biopsias de inmunocompetentes (1,2). los pacientes sintomáticos (9).…”
Section: Identificación De Cyclosporaunclassified
“…Materiales y métodos -posteriormente, lo definieron como la especie En la consulta médica del Colombiano Cyclospora cayetanensis (9,10), al demostrar con de Medicina Tropical se tiene como norma que, el microscopio electrónico que los ooquistes en los pacientes con diarrea de más de una tenian esporozoitos con organelos caracteristicos de duración, además del examen de las coccidias, phylum Apicomplexa. La coprológico para búsqueda de parásitos confirmación en el intestino se hizo al observar intestinales, se haga una preparación para las formas intraepiteliales del parásito en su colorearla por el método de Ziehl-Neelsen estadio asexual en las biopsias de intestino de modificado (9), Con este método se encontraron los pacientes sintomáticos (9,IO).…”
unclassified
See 1 more Smart Citation
“…The outbreaks of cyclosporiasis epidemiologically linked to contamination of berries or vegetables 10,13 have been consequently classified as foodborne, although contamination of field watering systems with the oocysts was possible. Epidemiologic circumstances presented in the cases, outbreaks, or non-outbreak settings of C. cayetanensis infections, 10,14 together with the prolonged pathogen sporulation period, 15 strongly indicate waterborne transmission of the oocysts. 16 It has been demonstrated that Corbicula fluminea clams are capable of recovery and sedimentation of infectious waterborne oocysts of Cryptosporidium parvum, 17,18 which is a pathogen with an oocyst diameter of 3.5-6.0-m.…”
mentioning
confidence: 99%